Diffraction and Scattering in Launchers of Quasi-Optical Mode Converters for Gyrotrons - Flamm, Jens Hanspeter (Karlsruher Forschungsberichte aus dem Institut für Hochleistungsimpuls- und Mikrowellentechnik, 2012)
In this work different methods for the calculation of diffraction and scattering in launchers of quasi-optical mode converters for gyrotrons are compared, ranked and extended. The extension gives the opportunity to take a tapered average radius of the waveguide antenna into account. The comparison and the extension of the fast field calculation methods for component synthesis opens the possibility to reduce diffraction and stray radiation of reliable and powerful millimeter wave sources.